Analysis of the long-term efficacy and safety of subcutaneous immunotherapy for atopic dermatitis - Zhou, Jie (Allergy Asthma Proc, 2021)
INTRODUCTION: Atopic dermatitis (AD) is a chronic and relapsing inflammatory skin disease characterized by severe pruritus and eczematous skin lesions. Subcutaneous immunotherapy (SCIT) refers to repeated contact with gradually increasing doses of allergen extracts, which improve patient tolerance to such allergens and controls, or reduces allergic symptoms. This study aimed to explore the long-term efficacy and safety of SCIT for patients with AD sensitized to house-dust mite (HDM). METHODS: We conducted a retrospective analysis of 378 patients with HDM-sensitized AD. Among these patients, 164 received SCIT plus pharmacotherapy for 3 years (SCIT group) and the other 214 patients received only pharmacotherapy (non-SCIT group). The scoring atopic dermatitis (SCORAD) and pruritus visual analog scale (VAS) scores, laboratory test results, and adverse effects were recorded. RESULTS: The SCORAD and pruritus VAS scores significantly decreased in the SCIT group. Also, the SCIT group showed higher reduction ratios of SCORAD and pruritus VAS scores than those observed in the non-SCIT group at 3 years after treatment initiation. The risk of development of new sensitization was higher in the non-SCIT group than in the SCIT group (relative risk 1.92 [95% confidence interval CI, 1.30–2.85]; p < 0.05). The eosinophil count of the participants significantly differed in the complete response (CR) group (p < 0.05) but not in the non–CR group (p = 0.098). However, the serum total immunoglobulin E value was not significantly reduced (p = 0.204). Of 8421 injections given to the patients, 231 injections (2.74%) showed adverse effects during the treatment period. CONCLUSION: Three years of SCIT can significantly reduce the severity and pruritus of moderate-to-severe AD with HDM sensitization. Patients who are multisensitized can also benefit from HDM SCIT. Patients can achieve long-term effects, such as prevention of neoallergen sensitization and inhibition of the allergy march.